Quo Vadis Pendidikan Agama Islam: Peluang dan Tantangan Pembelajaran PAI di Era Generasi Digital Native - Muhammad Candra Syahputra (CV. Eureka Artha Nusantara, 2026)
The Digital Native Generation, encompassing Generation Z and Millennials, has grown up in an environment characterized by instant access to digital technology and information, presenting a new paradigm in the world of education, including Islamic Religious Education (IRE). This study aims to analyze the opportunities that can be utilized and the challenges faced by IRE learning in responding to the distinctive characteristics of the digital native generation. The research method employed is a literature study with a qualitative approach through critical analysis of various relevant academic references and literature. The research results indicate that personalized learning, flexibility in learning time and space, and broad access to online learning resources are the main opportunities in developing IRE learning. However, significant challenges also arise, primarily related to the rampant spread of religious misinformation (hoaxes), low digital literacy, and the potential decline in the socio-emotional interaction quality of students. Therefore, IRE learning needs to transform from an indoctrinative approach towards an integrative IRE learning model that combines Islamic principles, technology, and exemplary behavior. This transformation is expected to create effective, contextual, and transformative IRE learning, fostering students who possess a moderate understanding of Islam, good digital literacy, and sustainable digital piety.